Evaluation of the performances of a single‐use duodenoscope: Prospective multi‐center national study. Issue 1 (7th April 2021) - Napoléon, Bertrand; Gonzalez, Jean‐Michel; Grandval, Philippe; Lisotti, Andrea; Laquière, Arthur E.; Boustière, Christian; Barthet, Marc; Prat, Frédéric; Ponchon, Thierry; Donatelli, Gianfranco; Vanbiervliet, Geoffroy
Abstract : Objectives: A single‐use duodenoscope (SUD) has been recently developed to overcome issues with endoscopic retrograde cholangiopancreatography (ERCP)‐related cross‐infections. The aim was to evaluate SUD safety and performance in a prospective multi‐centre study. Methods: All consecutive patients undergoing ERCP in six French centers were prospectively enrolled. All procedures were performed with the SUD; in case of ERCP failure, operators switched to a reusable duodenoscope. Study outcomes were the successful completion of the procedure with SUD, safety and operators' satisfaction based on a VAS 0–10 and on 22 qualitative items. The study protocol was approved by French authorities and registered (ID‐RCB: 2020‐A00346‐33). External companies collected the database and performed statistical analysis. Results: Sixty patients (34 females, median age 65.5 years old) were enrolled. Main indications were bile duct stones (41.7%) and malignant biliary obstruction (26.7%). Most ERCP were considered ASGE grade 2 (58.3%) or 3 (35.0%). Fifty‐seven (95.0%) procedures were completed using the SUD. Failures were unrelated to SUD (one duodenal stricture, one ampullary infiltration, and one tight biliary stricture) and could not be completed with reusable duodenoscopes. Median operators' satisfaction was 9 (7–9). Qualitative assessments were considered clinically satisfactory in a median of 100% of items and comparable to a reusable duodenoscope in 97.9% of items. Three patients (5%) reported an adverse event. None was SUD‐related. Conclusions: The use of a SUD allows ERCP to be performed with an optimal successful rate. Our data show that SUD could be used for several ERCP indications and levels of complexity.